Dissimilar ultrasonic spot welding of rare-earth containing ZEK100 magnesium-to-aluminum alloy with a zinc interlayer: Microstructural evolution and mechanical properties. (28th April 2023) - Peng, H.; Chen, D.L.; Guo, S.F.; Hong, H.; Zheng, K.H.; Bai, X.F.; Li, D.Y.; Jiang, X.Q.
Abstract: The purpose of the present study was to identify microstructural changes at both Mg/Zn and Al/Zn interfaces of ultrasonic spot welded joints between a rare-earth containing ZEK100 magnesium alloy and an AA6022 aluminum alloy with a zinc interlayer, focusing on their effect on the tensile lap shear strength. During ultrasonic spot welding (USW), the diffusion or reaction was observed to occur at both interfaces, with the reaction being much faster at the Mg/Zn interface than at the Al/Zn interface. This was attributed to the higher diffusion rate of Zn in Mg and lower eutectic temperature in the Mg-Zn system along with the higher specific heat capacity and lower thermal conductivity of magnesium. With increasing welding energy, the diffusion layer at both interfaces increased. However, the diffusion layer at the Al/Zn interface was appreciably thinner than that at the Mg/Zn interface. While the eutectic (or eutectoid) structure containing Mg7 Zn3, MgZn2 and MgZn intermetallic phases appeared at the Mg/Zn interface, the diffusion layer at the Al/Zn interface consisted of only Al and Zn based solid solution. The joining mechanisms were mainly mechanical interlocking and metallurgical bonding which were enhanced by grain refinement at both interfaces stemming from dynamic crystallization during USW. The peak tensile lap shear strength of the present Mg-Al dissimilar joints was attained at a welding energy of 1000 J, and the failure occurred in the diffusion layer at the Mg/Zn interface.